Effectiveness of Foliar Biofortification of Carrot With Iodine and Selenium in a Field Condition - Rakoczy-Lelek, Roksana; Smoleń, Sylwester; Grzanka, Marlena; Ambroziak, Krzysztof; Pitala, Joanna; Skoczylas, Łukasz; Liszka-Skoczylas, Marta; Kardasz, Hubert (Frontiers in Plant Science, 2021)
Iodine (I) and selenium (Se) are essential to human and animal development. There is a worldwide deficit of I and Se in the diet of humans, as well as in animals. It is advisable to enrich plants with these elements to ensure adequate uptake in animals and humans. The aim of this study was to determine the efficacy of the application of I and Se in the cultivation of carrot crops, to better understand the metabolic pathways and processes of I applied through foliar spray. Carrots were fertilized with four-fold foliar applications of iodine and selenium, which were applied as the liquid fertilizers "I+Se", "Solo iodine" and "Solo selenium", all containing an organic stabilizer, in two field trials. Foliar nutrient applications of I and Se were translocated by the plant for storage in the roots. The level of enriched I and Se in the roots was considered safe for the consumer. The Recommended Daily Allowance values for I and Se in the roots of 100 g of fresh carrots is 4.16% and 4.37%, respectively. Furthermore, I and Se accumulated in the roots to a level that was physiologically tolerated by carrot. Biofortification through foliar feeding did not impact negatively on the yield or quality of the carrot crop. Iodides applied via foliar application were the dominant form of I in the plant tissues and were included in the metabolic process of the synthesis of iodosalicylates, iodobenzoates, iodotyrosine (I-Tyr) and plant-derived thyroid hormone analogs (PDTHA). No synergistic or antagonistic interaction between I and Se, with respect to the effectiveness of biofortification in roots, was observed in any treatments. The molar ratio of I:Se in the roots after foliar application of both elements was approximately 1.6:1 and was similar to the control (1.35:1)